2022
DOI: 10.1021/acs.chemmater.2c02664
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Robust Imine-Linked Two-Dimensional Covalent Organic Frameworks in Supercritical Carbon Dioxide

Abstract: The traditional vacuum activation of covalent organic framework (COF) materials typically erodes the materials' crystallinity significantly and then reduces the surface area of isolated materials. Developing new methods for synthesizing robust COFs which could survive the duration of the vacuum activation process is of great practical significance. In this work, a robust imine-linked 2D COF TAPB-TA was creatively constructed in supercritical CO 2 (ScCO 2 ) with γ-valerolactone (GVL) as a cosolvent instead of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…108 Most COFs are synthesised using solvothermal conditions (typically between 120 and 150 °C), acid catalysts and high boiling point organic solvents such as mesitylene, 1,4-dioxane, or N , N -dimethylacetamide. 105 More sustainable and environmentally friendly syntheses have already been proposed by replacing organic solvents with water, 109,110 using supercritical CO 2 , 111 or solvent-free methods. 112 Microwave-assisted synthesis of COFs has also been extensively explored to considerably reduce reaction times.…”
Section: Other Parametersmentioning
confidence: 99%
“…108 Most COFs are synthesised using solvothermal conditions (typically between 120 and 150 °C), acid catalysts and high boiling point organic solvents such as mesitylene, 1,4-dioxane, or N , N -dimethylacetamide. 105 More sustainable and environmentally friendly syntheses have already been proposed by replacing organic solvents with water, 109,110 using supercritical CO 2 , 111 or solvent-free methods. 112 Microwave-assisted synthesis of COFs has also been extensively explored to considerably reduce reaction times.…”
Section: Other Parametersmentioning
confidence: 99%
“…Li et al used SC CO 2 and γ-Valerolactone (GVL) as a reaction medium to obtain iminelinked 2D COF 1,3,5-tris(4-aminophenyl)benzene/terephthalaldehyde (TAPB-TA). [216] During the synthesis process, SC CO 2 is proven to transform the fragile COF into a robust COF with maintaining high crystallinity and high surface area, compared to after vacuum activation, only postprocessing of SC CO 2 and solvent immersion-reactivation cycles. It is found that the sharp and more peaks intense XRD patterns and Raman spectra imply the higher crystallinity of Sc-COF, according to Figure 24b,c.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Reproduced with permission. [216] Copyright 2022, American Chemical Society. illustration of phase transformation from bulk Cu-BTC to 2D topological structure.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In an investigation by Xue et al, robust imine-linked 2D COFs were creatively fabricated by a green method using 1,3,5tris(4-aminophenyl)benzene/terephthalaldehyde monomers in supercritical CO 2 with γ-valerolactone as a co-solvent. [73] γ-Valerolactone is derived from biomass and has great features low toxicity, biodegradability, low vapor pressure, and good stability in both acidic and basic media. Also, supercritical CO 2 is a green solvent with zero surface tension, gas-like diffusivity, and viscosity as well as liquid-like density and solvating properties.…”
Section: Other Green Solventsmentioning
confidence: 99%